Regenerable‐Catalyst‐Aided, Opened to Air and Sunlight‐Driven "CuAAC&ATRP" Concurrent Reaction for Sequence‐Controlled Copolymer. Issue 22 (10th October 2017) - Zhang, Weidong; Xue, Wentao; Ming, Wen; Weng, Yuyan; Chen, Gaojian; Haddleton, David M.
Abstract: An ideal stimuli‐responsive controlled/living radical polymerization should have the ability to manipulate the reaction through spatiotemporal "on/off" controls, achieving the polymerization under fully open conditions and allowing for precise control over macromolecular architecture with defined molecular weights and monomer sequence. In this contribution, the photo (sunlight)‐induced electron transfer atom transfer radical‐polymerization (PET‐ATRP) can be realized to be reversibly activated and deactivated under fully open conditions utilizing one‐component copper(II) thioxanthone carboxylate as multifunctional photocatalyst and oxygen scavenger. The polymerization behaviors are investigated, presenting controlled features with first‐order kinetics and linear relationships between molecular weights and monomer conversions. More importantly, "CuAAC&ATRP" concurrent reaction combining PET‐ATRP, photodriven deoxygenation, and photoactivated CuAAC click reaction is successfully employed to synthesize the sequence‐defined multiblock functional copolymers, in which the iterative monomer additions can be easily manipulated under fully open conditions. Abstract : A novel and multifunctional photocatalyst, copper(II) thioxanthone carboxylate, based on the ability of the formation of Cu(I) for photoinduced atom transfer radical polymerization and photodriven copper(I)‐catalyzed azide‐alkyne cycloaddition reaction by photo (sunlight)‐induced electron transfer, and the in situ regeneration of Cu(II) for regenerating the photocatalyst and scavenging oxygen, is successfully employed to fabricate sequence‐defined functional materials.